PENGGUNAAN GADGET OLEH PESERTA DIDIK DALAM KEGIATAN PEMBELAJARAN GEOGRAFI DI SMA NEGERI KOTA PADANG - Utama, Emilia; Anwar, Syafri (JURNAL BUANA, 2025)
This research aims to find out the percentage of gadgets used by students at Padang City State High School to support geography learning activities and other interests, the use of gadgets influences the process and outcomes of students' geography learning as well as teachers' efforts to overcome the problem of gadget use at Padang City State High School, use gadgets at high school level between the center and the outskirts of Padang City. Using quantitative descriptive methods with purposive sampling techniques. This research data was obtained by interviews, questionnaires, and documentation and then analyzed using quantitative descriptive analysis. The research results show that the use of gadgets for learning purposes in schools in the city center has a percentage of 71% and schools on the outskirts of Padang City have a percentage of 72%. The use of gadgets for other purposes in schools in the center and on the outskirts of Padang City has the same percentage, namely 76%. The use of gadgets in the learning process and geography learning outcomes of students in schools in the city center and outskirts of Padang City shows the same percentage results, namely 75%. This percentage is included in the high category and does not show a significant difference between central schools and suburban schools. Teachers make curative efforts through outreach activities.